The identity of the Bahama endemic field cricket Gryllus bryanti Morse (Orthoptera: Gryllidae; Gryllinae; Gryllini) - Weissman, David B.; de Luca, Paul Anthony; Judge, Kevin A.; Gray, David A. (Zootaxa, 2019)
The Bahama endemic field cricket, Gryllus bryanti Morse, 1905, previously known from only the lost female holotype, is redescribed, including designation of a neotype. Known only from Andros and Eleuthera Islands in The Bahamas, where it occurs with G. assimilis, it can be separated from the latter by song, tegmen file characteristics, head wider than pronotum, and genetics.